Catalytic activity of morphology-tailored NiO–Ce0.8Gd0.2O2−δ synthesized by a hexamethylenetetramine (HMT)-assisted solvothermal process. Issue 10 (December 2015) - Rath, Manasa K.; Sahoo, Trilochan; Lee, Ki-Tae
Abstract: NiO–Ce0.8 Gd0.2 O2− δ (GDC) powders with controlled morphology were synthesized by a solvothermal process varying the hexamethylenetetramine (HMT) to precursor ratio. The formation of diverse morphologies as micro-flower, micro-cubes and micro-rods with different porosity were observed by varying the HMT to precursor ratio. The catalytic activity for the hydrogen oxidation reaction (HOR) and methane oxidation reaction (MOR) of the Ni–GDC anodes was studied by impedance spectra analysis using an yttria-stabilized zirconia (YSZ)-supported symmetry half-cell. Ni–GDC anode fabricated with 100HMT powder (100 wt% HMT) exhibited the least polarization resistivity of 2.59 Ω cm 2 and 26.3 Ω cm 2 measured at 750 °C under humidified H2 and CH4 flow, respectively. The Ni–GDC anode with better pore distribution exhibited the best electro-catalytic activity.